Corner Frequency in Induced Cracks in Laboratory Samples - Gaete-Garreton, L; Vargas-Hernandez, y (2012)
An experimental study of corner frequency in special samples prepared in laboratory it is presented. The samples were prepared to produce a controlled fault and the acoustic emissions in the failure time were recorded. Our finding shows that it is possible to detect signals from the sample fault. Also the corner frequency was calculated and some material constants were evaluated. It seems that the technique can being useful in the study of the rocks properties in the mines. © 2012 American Institute of Physics.